Long-term safety and efficacy of Omnitrope®, a somatropin biosimilar, in children requiring growth hormone treatment: Italian interim analysis of the PATRO Children study. Issue 1 (December 2016) - Iughetti, Lorenzo; Tornese, Gianluca; Street, Maria; Napoli, Flavia; Giavoli, Claudia; Antoniazzi, Franco; Stagi, Stefano; Luongo, Caterina; Azzolini, Sara; Ragusa, Letizia; Bona, Gianni; Zecchino, Clara; et al.
Abstract Background PATRO Children is an ongoing observational, longitudinal, non-interventional, global post-marketing surveillance study, which is investigating the long-term safety and effectiveness of Omnitrope®, a somatropin biosimilar to Genotropin®, in children with growth disturbances. The primary endpoint of PATRO Children is long-term safety and the secondary endpoint is effectiveness, which is assessed by analysing auxological data such as height (HSDS) and height velocity (HVSDS) standard deviation scores. Here, we report the data from the Italian interim analysis of PATRO Children data up to August 2015. Methods PATRO Children is enrolling children who are diagnosed with conditions of short stature requiring GH treatment and are receiving Omnitrope®. Adverse events (AEs) are assessed in all Omnitrope®-treated patients. Height is evaluated yearly to near-adult (final) height, and is herein reported as HSDS; height velocity is also assessed and reported as a standard deviation score (HVSDS). Results Up to August 2015, a total of 186 patients (mean age 10.2 years, 57.5 % males) were enrolled :156 [84 %] had growth hormone deficiency, 12 [6.5 %] were born small for gestational age, seven [3.8 %] had Prader-Willi syndrome, one [0.5 %] had Turner syndrome and one [0.5 %] had chronic renal insufficiency; seven [3.8 %] patients had other indication profiles. The mean treatment duration with Omnitrope® was 28.1 ± 19.1 months. AEs were reported in 35.6 % of patients and included headache, pyrexia, arthralgia, abdominal pain, leg and/or arm pain and increased blood creatine phosphokinase. Two serious AEs in two patients were thought to be drug-related; one patient experienced a minimal increase in a known residual craniopharyngioma, and another a gait disturbance with worsening of walking difficulties. Similar to investigational studies, Omnitrope® treatment was associated with improvements in both HSDS and HVSDS. Conclusions Omnitrope® appears to be well tolerated and effective for the treatment of a wide range of paediatric indications, which is consistent with the outcomes from controlled clinical trials. These results need to be interpreted with caution until the data from the global PATRO Children study are available.